2013
DOI: 10.1126/science.1233529
|View full text |Cite
|
Sign up to set email alerts
|

Holographic Vortex Liquids and Superfluid Turbulence

Abstract: Superfluid turbulence, often referred to as quantum turbulence, is a fascinating phenomenon for which a satisfactory theoretical framework is lacking. Holographic duality provides a systematic new approach to studying quantum turbulence by mapping the dynamics of certain quantum theories onto the dynamics of classical gravity. We use this gravitational description to numerically construct turbulent flows in a holographic superfluid in two spatial dimensions. We find that the superfluid kinetic energy spectrum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
117
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(123 citation statements)
references
References 43 publications
6
117
0
Order By: Relevance
“…Dipole-dipole collisions are particularly interesting in that vortex pair annihilation may occur during the collision. Vortex pair annihilation is one of the key issues in the study of 2D quantum turbulence [32][33][34][35][36][37][38][39][40]. Many aspects of the pair annihilation process [41,42], such as the roles of vortex-phonon interactions [43,44], and thermal dissipation [45], have never been directly addressed in experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Dipole-dipole collisions are particularly interesting in that vortex pair annihilation may occur during the collision. Vortex pair annihilation is one of the key issues in the study of 2D quantum turbulence [32][33][34][35][36][37][38][39][40]. Many aspects of the pair annihilation process [41,42], such as the roles of vortex-phonon interactions [43,44], and thermal dissipation [45], have never been directly addressed in experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Several works have considered the possibility of an inverse energy cascade in two-dimensional BECs, suggesting that the compressibility of the fluid may be fatal for largescale clustering, instead causing transport of energy to small scales driven by vortex dipole annihilation [56][57][58]. However, these works considered specific scenarios that immediately prohibited clustering, due to either starting from initial conditions dominated by acoustic energy [56,57], or evolving the system according to an overdamped equation of motion [58].…”
Section: B Motivation From Bose-einstein Condensatesmentioning
confidence: 99%
“…However, these works considered specific scenarios that immediately prohibited clustering, due to either starting from initial conditions dominated by acoustic energy [56,57], or evolving the system according to an overdamped equation of motion [58]. As shown in a systematic study of energy transport [44], a clear regime exists where energy is transported to large scales via a vortex clustering process.…”
Section: B Motivation From Bose-einstein Condensatesmentioning
confidence: 99%
“…An interesting question is whether the inverse cascade can occur in an atomic BEC. Since the enstrophy, proportional to the total number of quantized vortices in quantum turbulence, is not conserved in a compressible 2D superfluid due to the vortex-antivortex annihilation, there has been a theoretical controversy on this issue [11][12][13][14][15][16][17][18][19][20]. Recently, Neely et al [21] reported an experimental and numerical study to show that there are conditions for which 2D turbulence in a BEC can dissipatively evolve into large-scale flow.…”
Section: Introductionmentioning
confidence: 99%